Transforming Conflict through Insight - Melchin, Kenneth R., 1949- (Book collections on Project MUSE., 2008)
<Transforming Conflict through Insight demonstrates how applying Bernard Lonergan's philosophy of insight to mediation can lead to more productive and constructive negotiations.